A muscle specific protein “myoferlin” modulates IL-6/STAT3 signaling by chaperoning activated STAT3 to nucleus - Yadav, Arti (Oncogene, 2017)
Myoferlin, a member of ferlin family of proteins, was first discovered as a candidate gene for muscular dystrophy and cardiomyopathy. Recently myoferlin was shown to be also expressed in endothelial and cancer cells where it was shown to modulate VEGFR-2 and EGFR signaling by enhancing their stability and recycling. Based on these reports, we hypothesized that myoferlin might be regulating IL-6 signaling by modulating IL-6R stabilization and recycling. However, in our immunoprecipitation (IP) experiments, we did not observe myoferlin binding with IL-6R. Instead, we made a novel discovery that in resting cells myoferlin was bound to EHD2 protein and when cells were treated with IL-6, myoferlin dissociated from EHD2 and binds to activated STAT3. Interestingly, myoferlin depletion did not affect STAT3 phosphorylation, but completely blocked STAT3 translocation to nucleus. In addition, inhibition of STAT3 phosphorylation by phosphorylation defective STAT3 mutants or JAK inhibitor blocked STAT3 binding to myoferlin and nuclear translocation. Myoferlin knockdown significantly decreased IL-6-mediated tumor cell migration, tumorsphere formation and ALDH positive cancer stem cell population, in vitro. Furthermore, myoferlin knockdown significantly decreased IL-6-meditated tumor growth and tumor metastasis. Based on these results, we have proposed a novel model for the role of myoferlin in chaperoning phosphorylated STAT3 to the nucleus.